2021
DOI: 10.3390/proteomes9040039
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Proteomics to Understand Promotive Effect of Plant-Derived Smoke Solution on Soybean Root

Abstract: Plant-derived smoke solution enhances soybean root growth; however, its mechanism is not clearly understood. Subcellular proteomics techniques were used for underlying roles of plant-derived smoke solution on soybean root growth. The fractions of membrane and nucleus were purified and evaluated for purity. ATPase and histone were enriched in the fractions of membrane and nucleus, respectively. Principal component analysis of proteomic results indicated that the plant-derived smoke solution affected the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Membranes were isolated according to the manufacturer's instructions of the Mem-PER Plus Membrane Protein Extraction Kit (Thermo Fisher Scientific, San Jose, CA, USA) with some modifications. The procedures are described in a previous study [48] (Table S1).…”
Section: Isolation Of Membrane Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes were isolated according to the manufacturer's instructions of the Mem-PER Plus Membrane Protein Extraction Kit (Thermo Fisher Scientific, San Jose, CA, USA) with some modifications. The procedures are described in a previous study [48] (Table S1).…”
Section: Isolation Of Membrane Fractionsmentioning
confidence: 99%
“…An SDS-sample buffer consisting of 60 mM Tris-HCl (pH 6.8), 2% SDS, 10% glycerol, and 5% dithiothreitol was added to the protein extracts [52]. The quantified proteins (10 µg) were separated via electrophoresis on a 10% SDS-polyacrylamide gel and transferred onto a polyvinylidene difluoride (PVDF) membrane using a semidry transfer blotter (Nippon Eido, Tokyo, Japan) [48]. The blotted PVDF membrane was blocked for 5 min in a Bullet Blocking One regent (Nacalai Tesque, Kyoto, Japan).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…A soybean subcellular root protein study was performed using fractions of membranes and nuclei, resulting in 441 identified proteins. Plant-derived smoke solution increased soybean root growth through transcriptional promotion with RNA polymerase II expression and energy production with ATPase accumulation [ 43 ]. The use of the nuclei isolation/extraction kit (Sigma-Aldrich, St. Louis, MO, USA) is an easy and convenient methodology employed in many recent studies.…”
Section: Crop Subcellular Proteomicsmentioning
confidence: 99%
“…The combined effect of plant growth-promoting bacteria and PDS solution was more effective than the individual effect on rice [ 21 ]; however, they are both usually used individually to improve plant growth under saline conditions. In the case of soybean, PDS solution positively affected the post-germination growth [ 22 , 23 ]. Additionally, this solution enhanced soybean growth under flooding [ 24 ] and after flooding [ 25 ].…”
Section: Introductionmentioning
confidence: 99%